Dinamika mazhab Shafi’i dengan cara Aceh: Studi tentang praktik mazhab di kalangan tokoh agama - Zulkarnain Zulkarnain (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
This study of the dynamics of shafi’ite school tried to uncover the diversity of the views regardingcertain problems among the scholars of Shafi’ite school and between particular scholar and the imamShafi’i himself. This focus deal with the dynamics existed in the Shafi’ite books. It should be done in thewise manner, for the dynamics it self was triggered by the certain situation and condition, differentcontexts, space, time, geography, circumstance and the condition of the nature that give birth to thedifferent legal regulation. To understand the dynamics that occurred in those Shafi’ite books easily, wemay borrow the rules of Arabic syntax namely ‘ilm nahw, associated with the rule of istitsna’ whichconsisted of six letters; illa, ‘adaa, siwa, ghairu, khala and hasya. Those six letters have the same functionthat is the exemption, but the usage of each letter in the sentence has different rule in Arabic grammar.The dynamics rise dualism of Islamic jurisprudence in Aceh, in which the sharia court refer to theCompilation of Islamic Jurisprudence, while tengku ( local muslim scholars) in Dayah refer to the turasbook of Shafi’ite school. Slowly, the friction started between the legal decision issued by the sharia courtand the fatwas issued by the tengku of Dayah (local Islamic boarding school), for instance, the issue oftalaq, inheritance and other legal issues.